Influence of cage fish farming on the diet of dominant fish species of a Brazilian reservoir (Tiete River, High Parana River basin) - Ramos, I.P.; Vidotto-Magnoni, A.P.; Carvalho, Edmir Daniel [UNESP] (My University, 2008)
The cage farming of aquatic organisms was initiated 50 years ago, and was introduced to Brazil in the 1990's. In these systems, there is an input of organic matter from ration that is not totally used by the cage fishes, becoming available for the organisms of adjacent biota, including fish fauna. The aim of this work is to evaluate the interference in the diet of three dominant fish species (Plagioscion squamosissimus Heckel, 1840, Astyanax altiparanae Garutti and Britski, 2000 and Metynnis maculatus Kner, 1858) associated with ish cage farming. For determination of the diet, the Alimentary Index (AI) was used. In both stretches (around cage farm and control), P. squamosissimus selected aquatic insects, while A. altiparanae preferred terrestrial insects and M. maculatus eats ration remains. Diferences in abundance of these feeding resources found of the stomach content were observed among the two stretches. Thus, the small alterations in the diets of P. squamosissimus and A. altiparanae, indicate that cage farming can change the diet of resident species in reservoirs. This practice also influences the population structure of fish species, since higher middle standard lengths were found in A. altiparanae and P. squamosissimus populations resident around cage farms, in relation to the control stretch.

A utilização de sistemas de criação em tanques-rede iniciou-se há mais de 50 anos, sendo implantada no Brasil em meados de 1990. Nesses sistemas, há uma entrada de matéria orgânica decorrente do manejo, que se torna disponível para os demais organismos da biota adjacente, incluindo a fauna de peixes residentes. O objetivo deste trabalho é avaliar a influência da atividade de piscicultura em tanquesrede na composição da dieta das três espécies de peixes mais abundantes (Plagioscion squamosissimus Heckel, 1840, Astyanax altiparanae Garutti and Britski, 2000 and Metynnis maculatus Kner, 1858) atraídas por essa atividade. Para determinação da dieta utilizou-se o Índice Alimentar (IAi). Em ambos os trechos (tanquesrede e controle), P. squamosissimus apresentou preferência por insetos aquáticos, enquanto A. altiparanae por insetos terrestres e M. maculatus por restos de ração. Constata-se que há diferenças quanto à abundância desses itens alimentares encontrados no conteúdo estomacal entre os trechos estudados. Assim, infere-se que as pequenas alterações na dieta de P. squamosissimus e A. altiparanae, aliadas a dieta caracterizada para as três espécies alvo, quando comparadas com a literatura, indicam que os empreendimentos de piscicultura em tanques-rede alteram a dieta das espécies de peixes residentes nos reservatórios. Também, influenciam na estrutura populacional, visto que já foram evidenciados maiores comprimentos padrões médios nas populações de A. altiparanae e P. squamosissimus residentes no entorno dos tanques-rede em relação ao trecho controle.
Influência da piscicultura em tanques-rede na dieta de espécies de peixes dominantes de um reservatório brasileiro (Rio Tietê - bacia do alto Paraná)